Effect of postural angle on back muscle activities in aging female workers performing computer tasks - Kamil, N.S.M.; Md Dawal, Siti Zawiah (2015)
Purpose This study investigated the effects of postural angle on back muscle activity during a computer task in aging women. Subjects Seventeen women >= 50 years old participated. Methods The participants were instructed to perform computer-related tasks for 20 minutes on a workstation that simulated typical office working conditions. Back posture was measured from the measured trunk and pelvic angles. Electromyography activities were recorded simultaneously from the cervical erector spinae, longissimus, and multifidus muscles. Results The lowest mean percentages of maximum voluntary contraction for the cervical erector spinae and longissimus muscles were obtained when the upper trunk and pelvic angles were between 0 degrees to -5 degrees from the sagittal plane. The back muscle activities increased as the upper trunk and pelvic angles exceeded 0 degrees. Statistical analysis showed significant correlations between upper trunk angle and cervical erector spinae and longissimus muscle activities. Similarly, pelvic angle was significantly correlated with cervical erector spinae and multifidus muscle activities. Conclusion A neutral back posture minimizes muscle activities in aging women performing computer tasks.